2011
DOI: 10.1029/2010ja015827
|View full text |Cite
|
Sign up to set email alerts
|

On the statistical relation between ion upflow and naturally enhanced ion-acoustic lines observed with the EISCAT Svalbard radar

Abstract: We have investigated characteristics of ion upflow and naturally enhanced ion‐acoustic lines (NEIALs) based on the European Incoherent Scatter (EISCAT) Svalbard radar (ESR) data continuously obtained between March 2007 and February 2008. For the ion upflow study we have used approximately 78,000 field‐aligned profiles obtained with the ESR. For the NEIAL study we have identified approximately 1500 NEIALs in the ESR data at altitudes between 100 and 500 km. The occurrence frequency of ion upflow shows two peaks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 40 publications
3
23
0
Order By: Relevance
“…At high latitudes the spectral power in the ion acoustic regime is occasionally enhanced above the thermal backscatter. These so-called naturally enhanced ion acoustic lines (NEIAL) occur in the altitude range of 140 to 1900 km during magnetically disturbed conditions (Foster et al, 1988;Rietveld et al, 1991;Sedgemore-Schulthess and St. Maurice, 2001;Ogawa et al, 2006Ogawa et al, , 2011. The enhancements observed during NEIALs can be up to 4-5 orders of magnitude and are typically extended over hundreds of kilometers in altitude.…”
Section: Introductionmentioning
confidence: 99%
“…At high latitudes the spectral power in the ion acoustic regime is occasionally enhanced above the thermal backscatter. These so-called naturally enhanced ion acoustic lines (NEIAL) occur in the altitude range of 140 to 1900 km during magnetically disturbed conditions (Foster et al, 1988;Rietveld et al, 1991;Sedgemore-Schulthess and St. Maurice, 2001;Ogawa et al, 2006Ogawa et al, , 2011. The enhancements observed during NEIALs can be up to 4-5 orders of magnitude and are typically extended over hundreds of kilometers in altitude.…”
Section: Introductionmentioning
confidence: 99%
“…NEIALs are observed as enhancement of ion line shoulders over a wide altitude range (several hundred kilometres), with several order-of-magnitude increases of one or both ion line shoulders -and no features with a zero Doppler shift. While NEIALs have been found to be related to soft precipitation, both statistically (Ogawa et al, 2011) and on an event basis (e.g. Sullivan et al, 2008), the SLT-like anomalous echoes in this study were found to be closely related to energetic precipitation, characteristic of discrete aurora.…”
Section: Discussionmentioning
confidence: 81%
“…However, these observations refer to a case without electron plasma wave activity. In studies of ion upflow and naturally enhanced ion lines, 58 it was found that NEIALs were found predominantly at enhanced electron-ion temperature ratios. Under these conditions it is possible that ion and electron holes can have a more important role than in our simulations.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the enhanced temperature ratios T e =T i ! 2 observed in some experiments 58 will allow longlived ion phase-space vortices.…”
Section: Discussionmentioning
confidence: 99%